EFEKTIVITAS PROGRAM BANTUAN PRESIDEN PRODUKTIF UNTUK USAHA MIKRO (BPUM) TERHADAP KINERJA PERKEMBANGAN USAHA MIKRO SELAMA MASA PANDEMI COVID-19 DI KELURAHAN BANJAR KECAMATAN BANJAR KOTA BANJAR - Nova Chalimah Girsang; Riza Purnama (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The impact of the Covid-19 outbreak, impacted the sluggish economic activity of MSMEs, around 65% of the national GDP was contributed by MSMEs in 2019. State funds disbursed for the BPUM program amounted to 21 trillion. With a very large state finances, the fast time to be realized, it must have caused a lot of problems. This requires research on the effectiveness of this program. The purpose of this study was to analyze the effectiveness of the Productive Presidential Assistance for Micro Enterprises (BPUM) program on the performance of microbusiness development during the Covid-19 pandemic in Banjar District, Banjar District, Banjar City. A quantitative approach is used to analyze how much influence the effectiveness of the BPUM program has on the business performance of MSMEs in the Banjar District, Banjar District, Banjar City. From the calculation of Correlation Coefficient of Correlation and Determination of the Summary Model, the results of calculating the level of relationship with a value of 0.782 are obtained. From the calculation of the correlation is included in the strong category. So there is a strong relationship between the Effectiveness of the BPUM Program on the Performance of Micro Enterprises in the Banjar District, Banjar District, Banjar City. The regression equation with a positive b value indicates that the effectiveness of the BPUM program on service quality has a positive influence. This means that the effectiveness of the BPUM program increases, the performance of micro-enterprises in Banjar sub-district, Banjar sub-district, Banjar city also increases.